The Effectiveness of Audiovisual Media and Snakes and Ladders Games on Increasing Knowledge and Skills of Brushing Teeth in Early Childhood Jambi City - Willia Novita Eka Rini; Adelina Fitri; Vinna Rahayu Ningsih (Universitas Airlangga, 2025)
Background: Dental health is the most important part of general oral health, especially during a child's growth and development. Children with dental caries experience loss of chewing ability and problems with digestion, resulting in disruption of growth and development. Dental caries in children is still a fairly high prevalence problem in Indonesia. Aims: This research aimed to see the effect of audiovisual media to Increasing Knowledge and Skills of Brushing Teeth in Early Childhood. Methods: This study used a pretest-posttest control group design. The subjects of this study were PAUD students in Jambi City with a 1:1 ratio of respondents, where the experimental group was 40 students and the control group was 40 students. Primary data can be collected through various methods, such as surveys, interviews, direct observation, or scientific experiments. Data analysis employed the paired t-test. Results: The measurable test shows a p-value of 0.000 < 0.05. It indicates that the understanding of the students in the intervention group and the control group differs significantly. The analysis's findings indicate a significant difference between the students' skills in the intervention group and the control group, with a p-value of 0.000 <0.05. Conclusion: Audiovisual media and snake and ladders games are effective in increasing knowledge and skill of brushing teeth in early childhood.